7.3k views
3 votes
(x2 + 3x – 4) + (2x3 - 2x + 5)​

User Neapolitan
by
4.9k points

2 Answers

2 votes

Answer:

below

Explanation:


( x^(2) + 3x - 4) + ( 2x^(3) -2x = 5) \\x^(2) + 3x - 4 + 2x^(3) - 2x + 5 \\x^(2) + (3x-2x) + 2x^(3) + ( 5 - 4) \\ x^(2) + x + 2x^(3) + 1 \\ 2x^(3) + x^(2) + x + 1

(x2 + 3x – 4) + (2x3 - 2x + 5)​-example-1
User Wowsk
by
5.1k points
1 vote

Answer:

step-by-step.

x2+3x−4+2x3−2x+5

=x2+3x+−4+2x3+−2x+5

Combine Like Terms:

=x2+3x+−4+2x3+−2x+5

=(2x3)+(x2)+(3x+−2x)+(−4+5)

=2x3+x2+x+1

Answer:

=2x3+x2+x+1

User Maskacovnik
by
5.0k points